How to assess the quality of psychotherapy outcome studies: A systematic review of quality assessment criteria. (2nd September 2016) - Liebherz, Sarah; Schmidt, Nele; Rabung, Sven
Abstract: Objective : Although it is widely accepted that the quality of a study may affect its results, there is no agreed specific standard for assessing the quality of psychotherapy outcome studies. This study aims to review the existing variety of relevant quality assessment criteria.Method : We identified relevant quality measures based on a systematic literature search. To determine the specific relevance of the available quality criteria, we consulted experts in the field of psychotherapy outcome research.Results : Nineteen different measures providing 185 different quality criteria were included. Four measures specifically focused psychotherapy studies, none of these were designed for studies without a control group. Experts did judge 20% of the items as "absolutely indispensable."Conclusions : Quality criteria that are exclusively related to the context of psychotherapy research are rare. Further research is required to examine the empirical relation between specific quality criteria and study results.